AKTIVITAS ANTIINFLAMASI EKSTRAK ETANOL DAUN SEMANGGI AIR (Marsilea crenata) PADA MENCIT PUTIH (Mus musculus L.) DENGAN INDUKSI KARAGENIN - Fatimah, Siti; Suprasetya, Edy; Yogi Hernawan, Jarot (Politeknik Kesehatan Permata Indonesia Yogyakarta, 2024)
Inflammation is a complex biological response to stimulation that damages tissue with signs such as erythema (redness), dolor (heat), edema (swelling) and pain. Water clover (Marsilea crenata) has phytochemical compounds in the form of reducing sugars, steroids, carbohydrate content, and flavonoids as antioxidant agents. The aim of the research was to determine the anti-inflammatory activity of ethanol extract of water clover leaves (Marsilea crenata) as a natural antioxidant in white mice (Mus musculus L.) with carrageenin induction. The samples in this study were water clover leaves (Marsilea crenata) and were tested on white mice with different extract doses. The research was experimental using a completely randomized design (CRD) with different concentrations of extract doses and the movement of mice was observed. The stretching data was analyzed statistically using the one way ANOVA test with a confidence level of 95% (α=0.05) if there was significance, followed by the Tukey test to determine the differences between concentration treatments. The results showed that the percentage of anti-inflammatory protection from the negative control group was 61.14%, the 50 mg/kgBB dose group was 22.82%, the 100 mg/kgBB dose extract group was 37.14%, and the 200 mg/kgBB dose group was 70.15%. %. From these results it is known that the antioxidant activity of the ethanol extract of water clover (Marsilea crenata) with an extract dose of 200 mg/kgBW showed the best activity compared to other doses. Keyword : water clover, anti-inflammatory, percent protection